Self-assessment of the Feelings and Thoughts of Healthcare Professionals Regarding Their Social Lives and View of the Profession at the Onset and at the End of the First Year of the COVID-19 Pandemic - Özlem Tolu Kendir; Nilgün Erkek; Ramazan Gürlü (Galenos Yayinevi, 2023)
Introduction:We aimed to self-evaluate the impact of front-line health workers' perspective on their profession, family, social life and to determine how emotions and thoughts changed in the process.Methods:This is a questionnaire answered according to a 5-point Likert scale, which involved the demographic characteristics of the staff and the self-assessment of their views on their profession, family, and social life. Evaluations were made in the categories of occupational satisfaction, individual fear, professional ethics, meeting physical needs, trust in institution-infrastructure support, trust in the work team, and the effects on family life through categorized queries. Volunteer healthcare staff work actively in the units, where the patients with suspected or diagnosed infection were treated, included in the study. A year later, the questionnaire was administered again. The multiple logistic regression model was used to determine the factors.Results:Regarding the first year of the pandemic, no significant difference was determined in the individual fear of getting sick and professional ethics scores of healthcare professionals in Turkey. The scores of meeting physical needs, trust in the team, and institutional infrastructure support in the working environment were significantly decreased (p<0.05). While working conditions affected the family significantly (p<0.05), ethical behavior scores were above the average in both periods.Conclusion:The study reveals a profile of healthcare staff who maintain their professional ethical behaviors, are satisfied with their profession and can tolerate the impact of working conditions on family order, despite the drawbacks of the ongoing fear of getting sick.